The The Influence of Destination Image on Visit Intention in the Halal Tourism Destination of the Aceh Tsunami Museum with Destination Familiarity as a Moderating Variable - Fathin, Annidha; Halim, Hendra; Ginting, Ledy Mahara; Nurlina, Eka; Amri, Khoirul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the impact of destination image on visit intentions to the halal tourism attraction of the Tsunami Museum Aceh. The sample consists of 100 respondents who have visited the Tsunami Museum Aceh at least once. The data analysis technique used is Moderate Regression Analysis (MRA). The results indicate that the destination image has a positive and significant effect on visit intentions to the halal tourism attraction of the Tsunami Museum Aceh. Furthermore, the destination familiarity variable moderates the effect of destination image on visit intentions. However, since the regression coefficient is negative, destination familiarity weakens the influence of destination image on visit intentions. Based on these findings, it can be concluded that a destination image built through promotion and communication aligned with visitor values affects tourist visit intentions.